Integrating Social Support, Digital Competence, and Academic Self-Efficacy to Predict Academic Stress Among University Students: A PLS-SEM Analysis - Muhammad Al Fikhri; Zadrian Ardi; Ade Herdian Putra (KONSELOR, 2026)
Academic stress is one of the main problems faced by university students, especially in the context of increasingly digitised learning. This study aims to analyse the roles of social support and digital competence in academic stress, and to test the function of academic self-efficacy as a mediating and moderating variable in this relationship. This study uses a quantitative, survey-based approach, involving 888 students as respondents. Data were collected using a Likert-scale questionnaire and analysed using Partial Least Squares-based Structural Equation Modelling (PLS-SEM). The results show that social support significantly affects digital competence and academic self-efficacy. Digital competence and academic self-efficacy also have significant effects on academic stress, but in opposite directions. Mediation analysis revealed that social support has multiple indirect mechanisms for academic stress via digital competence and academic self-efficacy. In addition, the moderation results showed that academic self-efficacy can alter the strength of the relationship between social support and digital competence in relation to academic stress. These findings confirm that student academic stress is influenced by the complex interaction between social, psychological, and digital factors. This study contributes to the development of a conceptual model of academic stress and provides practical implications for strengthening guidance and counselling services in higher education.